The relevance of the school governance body to the effective decolonisation of education in South Africa - Duku, N.; Salami, I. A. (Faculty of Education, University of the Free State, 2017)
Decolonisation of education is understood in this paper as a means of formalising indigenous culture and knowledge within the formal school system. The focus of this paper is to see how the School Governance Body (SGB) can bring about decolonised education for sustainable development. The African societal culture and traditions seem to be misunderstood and side-lined today because of the privilege enjoyed by western values in formal education used to develop African children. The involvement of people at the grass roots who are still endowed with vast knowledge on this cultural heritage should be considered as an option. The South African school system gave room for community participation in the administration and management of schools under the system of School Governing Bodies (SGBs). These bodies have the potential of being a good source of indigenous knowledge and culture to the school system that will make the education more relevant and functional; hence, leading to sustainable development, if it is properly planned and tapped into. For this to happen, there is the need to examine the relevance of the body through close analysis of its composition and strength to assist in the decolonisation of education. This study adopted an ethnography approach of qualitative research. Three rural-based Eastern Cape communities were used where 18 parents participated in the study. Data were gathered through key informant interviews (KII) and focus group discussions (FGD). One of the results is that traditional leaders are part of the SGB, which makes it a good source of indigenous knowledge and traditions. It was recommended that the composition of the members of SGBs should statutorily include a recognised knowledgeable individual (RKI) in the community to make the body a good source of indigenous knowledge.
Keywords: School governance; Tradition; Culture; Indigenous knowledge; Africanisation; Education decolonisation